Study of silicon surface implanted by silver ions. (January 2019) - Stepanov, A.L.; Nuzhdin, V.I.; Valeev, V.F.; Vorobev, V.V.; Rogov, A.M.; Osin, Y.N.
Abstract: Ag + -ion implantation of single-crystal c -Si at low-energy ( E  = 30 keV) high-doses ( D  = 1.25⋅10 15 –1.5⋅10 17 ion/cm 2 ) and current density ( J  = 2, 8, 15 μA/cm 2 ) was carried out. The changes of Si surface morphology after ion implantation were studied by scanning electron and atomic force microscopy. The near surface area of samples was also analyzed by diffraction of the backscattered electrons and energy-dispersive X-ray microanalysis. At the lowest implantation doses of c -Si amorphization of near-surface layer was observed. Ag nanoparticles were synthesized and uniformly distributed over the near Si surface when the threshold dose of 3.1⋅10 15 ion/cm 2 is exceeded. At a dose of more than 10 17 ion/cm 2, the formation of a surface porous Si structure was detected. Ag nanoparticle size distribution function becomes bimodal and the largest particles were localized along Si-pore walls. Highlights: At a value of D  = 1.3⋅10 14 ion/cm 2, the near-surface region of Si is completely amorphized. Starting with D  = 3.1⋅10 15 ion/cm 2, Ag nanoparticles are nucleated in the α-Si layer. With further growth of D an increase in the amount of nanoparticles is observed. At D  = 1.5⋅10 17 ion/cm 2, the formation of open pores is observed on the surface of implanted Si. The size distribution of Ag nanoparticles becomes bimodal, consisting of two fractions: small - 5-10 nm and large - 40-50 nm.